The Effectiveness of Estafet Writing Strategy Using Padlet Application on Students Writing Skill : Penelitian - Fitriyah, Adinda Nurul; Asari, Slamet; Ma'rifah, Ulfatul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to examine the effectiveness of the estafet writing strategy using the Padlet application on eighth-grade students’ descriptive writing skills. A quasi-experimental design with pretest-posttest was applied to two classes, consisting of an experimental group using estafet writing via Padlet and a control group using conventional methods. Data were collected through written tests and analyzed using independent-samples t-tests. The results showed that the experimental group achieved higher posttest scores (mean = 79.57) compared to the control group (mean = 74.54), indicating that combining estafet writing with Padlet significantly improved students’ ability to generate ideas, organize sentences, and develop vocabulary. This finding suggests that integrating digital collaborative media with interactive writing strategies enhances students’ engagement and writing performance